1/2 -1/2(x+3)=1/6
1/2(x+3)=-1/3
x+3=-2/3
x=-7/3
Ai ủng hộ cho 1 li-ke đi mọi người
1/2-1/2 .(x+3)=1/6
1/2.(x+3) =1/2-1/6
1/2.(x+3) =1/3
x+3 =1/3:1/2
x+3 =2/3
x = -7/3
1/2 -1/2(x+3)=1/6
1/2(x+3)=-1/3
x+3=-2/3
x=-7/3
Ai ủng hộ cho 1 li-ke đi mọi người
1/2-1/2 .(x+3)=1/6
1/2.(x+3) =1/2-1/6
1/2.(x+3) =1/3
x+3 =1/3:1/2
x+3 =2/3
x = -7/3
A= ( 6 : 3/5 - 1 1/6 x 6/7 ) : ( 4 1/5 x 10/11 + 5 2/11 )
B= ( 1 - 1/2 ) x ( 1- 1/4 ) x ... x ( 1 - 1/2003 ) x ( 1 - 1/2004 )
C= 5 9/10 : 3/2 - ( 2 1/3 x 4 1/2 - 2 x 2 1/3 ) : 7/4
Tìm x
2.(x-5)-3(x+6)+=4(x-7)3(x-1)-2(x+5)=2(x-3)5(1-x)-6(1+x)=7(3-x)2x+5-3(3x+7)=6(1-x)+8x-2+3(x-4)=5(x-6)+7x+2+3(1-x)-5(2-x)=6(1-x)+(3-x)Bài 1: Tìm x :A) 3/4.(x-2) - 1/2.(6-2.x)= 1/6.x + 5
B) -1/2.(3.x + 5) - 2/3.(9-6.x) = 3/5.(x-10) - 3
C) (1/4.x - 1,5) + (5/6.x - 3) - (5/8.x -0,5) = -4,5
a, [ 2 và 1/3 + 3 và 1/2] .x= -4 và 1/-6 + 3vaf 1/7
b, x:( 3 và 1/2 - 5 và 1/6) -x =1 và 1/5 + 6 và 2/3
1 Tìm x:
a) 5.(1-x)-6.(1+x)=7.(3-x)
b) 2.(x+5)-3.(3x+7)=6.(1-x)+8x
c) x-2+3.(x-4)=5.(x-6)+7
d) x+2+3.(1-x)-5.(2-x)=6.(1-x)+7.(3x)
Tìm x:
a) 2 3/4 - x=3/4
b) x:5/6=-3/5
c)1 1/3 +2/3:x=1
d) x-1/9=8/3
e) 1/2 x + 650%x-x= -6
g) 2(x - 1/2) + 3(-1+x/3)=x(2/x - 1) (x khác 0)
h) x-2/20= -5/2-x
i) (x/2-1)3 + 2=-11/8
k) (x/3 +1/2) (75% - 1 1/2x)=0
GIÚP MÌNH VỚI Ạ. CẢM ƠN MỌI NGƯỜI!
a,x - 1/2 - (-1/6)
b,x + 5/6 = 3/8
c,2/3 . x -1/2 = 5/6
d, x/7 = 6/-21
e,(7/3 x -0,6) : 3^2/5 = 1
f,x/45 = 5/6 + -29/30
g,(4,5 - 2x) . (-1^4/7) =11/14
h,-2/7 + 4/7x=5/7
Tìm x
1) -5(x + 1/5) - 1/2(x -2/3) = 3/2x - 5/6
2) 3(x - 1/2) - 5(x + 3/5) = -x + 1/5
3) 3(3x - 1/2)3 + 1/9 = 0
4) 60% .x + 2/3x =1/3 . 6/1/3
Bài 1.(2,5 điểm)Tìm x, biết:
a) \(\left(2\dfrac{1}{3}+3\dfrac{1}{2}\right).x=-4\dfrac{1}{6}+3\dfrac{1}{2}\)
b) \(\left(1\dfrac{1}{3}+3\dfrac{1}{2}\right).x=4\dfrac{1}{6}-3\dfrac{1}{2}\)
c) \(\dfrac{1}{3}-\dfrac{7}{8}.x=\dfrac{1}{4}\)
d) \(\dfrac{3}{2}.x+\dfrac{1}{7}=\dfrac{7}{8}.\dfrac{64}{49}\)
e) \(5\dfrac{1}{2}-\left(\dfrac{1}{4}.x+\dfrac{2}{5}\right)=25\%\)